Comparative study on the high-temperature oxidation resistance of porous and solid TiNi-based alloys. (8th April 2021) - Marchenko, Ekaterina; Baigonakova, Gulsharat; Dubovikov, Kirill; Yasenchuk, Yuri; Chekalkin, Timofey; Obrosov, Aleksei
Abstract: The present work aims to characterize the surface features of solid and porous (sintered and SHS) TiNi-based alloys subjected to oxidation at 1000 °C in static air in the context of their resistance to high-temperature atmospheric attack. Clear differences between the intact and oxidated surfaces indicate the complexity of a chemicothermal diffusion process evolving therein. Microscopic and XRD studies showed that the dominant superficial constituent in all oxidated samples is titanium dioxide in the rutile modification. The phase and structural properties of the surface layers suggest that porous sintered and solid alloys are most susceptible to high-temperature corrosion due to bare reactive surfaces, which negatively affects their overall biocompatibility. Surface morphology analysis revealed microporous and loose superficial layers having a thickness of 8–10 and 50–60 μ m, respectively in the solid and sintered alloy. Also, these alloys showed a high content of leaching NiO and free Ni within the surface layer. Conversely, a thin (0.5–0.6 μ m), dense, and multifarious layer of oxycarbonitrides Ti4 Ni2 (O, N, C) concealing the porous SHS-TiNi matrix inhibits the negative effect of high-temperature oxidation.